Poverty Alleviation from an Islamic Perspective: Study of LazisNU Ponorogo Programs - Arsyadani, Achmad Arfinanto; Wahyudi, Amin (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Poverty is a deep-rooted social issue that demands serious attention in its resolution. Islam rejects poverty, considering it a calamity that must be fought, while social welfare is a shared responsibility, as outlined in Article 34 and Article 27 Paragraph 2 of the 1945 Constitution. Despite the government's efforts to alleviate poverty since independence, the results could have been more optimal. This study employs a descriptive qualitative method, collecting data through interviews, observations, documentation, and literature analysis. It also examines Islamic poverty alleviation through a NU Care-LAZISNU Ponorogo case study, which manages zakat, infaq, and sedekah to assist people experiencing poverty. The findings of this study highlight the need to apply Islamic economic principles in social and economic policies to reduce inequality and improve social welfare in Indonesia.